Expression of beta-human chorionic gonadotropin (beta-hCG) in non-trophoblastic elements of transitional cell carcinoma of the bladder: possible relationship with the prognosis. - Bacchi, C. E.; Coelho, Kunie Iabuki Rabello [UNESP]; Goldberg, José [UNESP] (My University, 1993)
Transitional cell carcinoma (TCC) of the bladder is a neoplasm with variability in its clinical behavior. Although there are several studies correlating stage and ABO isoantigen expression with invasiveness, there is no single predictor factor to assess the potential invasiveness, especially in the low grade, non-invasive TCC. In the present study we evaluated the correlation of histological grade plus stage and the expression of beta human chorionic gonadotropin (beta-hCG), in 100 cases of TCC, with the clinical behavior. These features were correlated with tumor progression in patients with at least two years of follow up. We observed more aggressiveness in G4 group (high grade and invasive) (93% had tumor progression) when compared to G1 group (low grade and superficial) (11% had tumor progression). However in 25.5% of the TCC cases (groups G2: low grade and invasive and G3: high grade and superficial) the clinical behavior was intermediate, showing some limitation in using grading and staging only, as a predictive factor. There was an expression of beta-hCG in 21.4% of the cases in up to 25% of the tumor cells without any trophoblastic morphology. These beta-hCG producing TCC had a strong correlation with aggressiveness: 39.1% and 12.8% of the TCC expressed beta-hCG with and without tumor progression, respectively.
Keywords: chorionic gonadotropin; adult; aged; bladder tumor; cancer invasion; cancer staging; chemistry; comparative study; female; follow up; human; immunochemistry; male; pathology; prognosis; transitional cell carcinoma; Adult; Aged; Aged, 80 and over; Bladder Neoplasms; Carcinoma, Transitional Cell; Chorionic Gonadotropin; Comparative Study; Female; Follow-Up Studies; Human; Immunochemistry; Male; Middle Age; Neoplasm Invasiveness; Neoplasm Staging; Prognosis